Perancangan Sistem Informasi Laporan Keuangan Berbasis Web Dengan Model RAD Pada Apotek Cavita Farma - Handayani, Rani Irma; Fakhrudin, Aziz; Normah, Normah (BINA INSANI ICT JOURNAL; Vol 11 No 2 (2024): Bina Insani ICT Journal (Desember) 2024, 2024)
The importance of an information system in a business, especially the accounting information system in the Cavita Farma pharmacy, can make recording activities seem long and less efficient. Recording financial reports that are still manual will make errors in writing data so that a great deal of time will be lost. The design of this accounting information system is a breakthrough in solving existing problems, especially problems with the accounting system. In constructing this method of accounting information, the rapid application development method was used, This approach was selected because to its capacity to create apps and makes it easier to solve problems more optimally. The input and output of the software are the main emphasis of this study's findings, whether the system can run properly and whether it is functional. Cavita Farma Pharmacy will find it easier to enter accounting data into the web- based accounting information system with the findings of this study.   Keywords : accounting information system, rapid application development, recording